Efficient GHz electro-optical modulation with a nonlocal lithium niobate metasurface in the linear and nonlinear regime - Agostino Di Francescantonio; Alessandra Sabatti; Helena Weigand; Elise Bailly-Rioufreyt; Maria Antonietta Vincenti; Luca Carletti; Jost Kellner; Attilio Zilli; Marco Finazzi; Michele Celebrano; Rachel Grange (Nature Communications)
Abstract Electro-optical modulation is essential in optical signal processing and laser technology, yet modulators based on the Pockels effect in flat optics lag behind bulk and integrated platforms in efficiency and speed. We bridge this gap realizing a metasurface based on lithium niobate (LiNbO₃) on insulator that leverages on resonances with quality-factor as high as 8000 to achieve fast electrical modulation of both linear and nonlinear optical properties. LiNbO3, well known for its high nonlinear susceptibility and wide transparency window across the infrared and visible spectrum, is employed to realize an asymmetric, one-dimensional array of nanowires, exhibiting resonances with linewidth <0.2 nm. The metasurface achieves a reflectivity modulation around 0.1, with a modulation efficiency, defined as relative modulation per applied Volt, larger than 0.01 V−1 on a −3 dB (−6 dB) bandwidth of about 800 MHz (1.4 GHz). Additionally, we demonstrate more than one order of magnitude intensity modulation of the second harmonic seeded by a continuous-wave laser, with a modulation efficiency of about 0.12 V−1. This dual modulation capability, rooted in the interplay between optical resonances and electric field manipulation, holds significant potential for cutting-edge applications in high-speed photonics, nonlinear optics, and reconfigurable communication systems.